2013
DOI: 10.5897/jeif2013.0517
|View full text |Cite
|
Sign up to set email alerts
|

Sources of real exchange rate volatility in the Ghanaian economy

Abstract: Real exchange rate volatility is an important contributor to risks in the financial world. During periods of excessive fluctuations in exchange rates, foreign trade and investments could be affected negatively. The objective of this study is to determine the sources of exchange rate volatility in Ghana. The methodology employed is a dynamic econometric technique based on the Autoregressive Distributed Lag (ADL) Model to account for psychological inertia among others. The study used annual data covering the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 26 publications
2
14
0
Order By: Relevance
“…Significance of the error term confirms the results of the Johansen's cointegration test, it also reflects that if we insert a shock to one of the variables of the model then 32.3% will be the speed of adjustments of the disequilibrium quarterly. This is sufficient to reject any no cointegration hypothesis and confirm the presence of a stable long-run relationship between RER and its determinants and that is consistent with the previous studies [16,18,3,19,1,23,21,11,25]. The estimate of ECM can be explained as follows; in the absence of any other shocks, the gap between the current RER and the equilibrium one can be reached within approximately 3 quarters of the year, while in other developing countries might need shorter period of time to reach equilibrium [ 3,18,23] Also, the results in Table 5 show the adjustment coefficients for the set of variables used in the investigation along with the short run dynamics.…”
Section: Vector Error Correction Model (Vecm)supporting
confidence: 90%
See 1 more Smart Citation
“…Significance of the error term confirms the results of the Johansen's cointegration test, it also reflects that if we insert a shock to one of the variables of the model then 32.3% will be the speed of adjustments of the disequilibrium quarterly. This is sufficient to reject any no cointegration hypothesis and confirm the presence of a stable long-run relationship between RER and its determinants and that is consistent with the previous studies [16,18,3,19,1,23,21,11,25]. The estimate of ECM can be explained as follows; in the absence of any other shocks, the gap between the current RER and the equilibrium one can be reached within approximately 3 quarters of the year, while in other developing countries might need shorter period of time to reach equilibrium [ 3,18,23] Also, the results in Table 5 show the adjustment coefficients for the set of variables used in the investigation along with the short run dynamics.…”
Section: Vector Error Correction Model (Vecm)supporting
confidence: 90%
“…Similarly other studies revealed that Government expenditures negatively affect RER [16,18,3,19]. The results of cointegration analysis showed there is a long run equilibrium association among the variables.…”
Section: Introductionsupporting
confidence: 58%
“…Thus exchange rate is higher for industries that have low mark-up ratios and those in the non-durable goods sectors. Specifically, on Ghana, studies on the effect of exchange rate on manufacturing firms' performance appears to be very scanty as most of the studies has focused on the effect of exchange rate (see for example Salifu et al, 2007;Nyarko et al, 2011;Mensah et al, 2013;Gyimah-Brempon & Gyapong, 1993;Opoku-Afari et al, 2004;Alagidede & Ibrahim, 2017;Bhattarai & Armah, 2005;Kyereboah-Coleman & Agyire-Tettey, 2008;Frimpong & Adam, 2010;Insah & Chiaraah, 2013) on economic growth, foreign direct investment, employment growth, capital inflows, trade balance, and exchange rate pass through effect. Notwithstanding from the empirical review and to the best of our knowledge we are aware of only two studies that examine the effect of exchange rate on manufacturing firms in Ghana with different focus (see for instance Abdul-Mumuni, 2019; Boateng, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus exchange rate fluctuations has led to the collapse of most manufacturing firms and also created an atmosphere of macroeconomic uncertainty which leads to a reduction in firms' profit, reduces employment levels as well as investment levels and also decreases in firm productivity. In spite of the above empirically, (see for instance Ofori et al, 2018;Alagidede & Ibrahim, 2017;Salifu et al, 2007;Nyarko et al, 2011;Mensah et al, 2013;Insah & Chiaraah, 2013;Bhattarai & Armah, 2005;Frimpong & Adam, 2010;Kyereboah-Coleman & Agyire-Tettey, 2008;Opoku-Afari et al, 2004;Gyimah-Brempon & Gyapong, 1993), very little is known on the effect of exchange rate fluctuations on manufacturing firms' performance in Ghana. Notwithstanding, there is evidence of the effect of exchange rate fluctuations on economic growth, capital inflows, trade balance, employment and growth in the empirical literature (see for instance Elbadawi et al, 2008;Umaru et al, 2018;Alagidede & Ibrahim, 2017;Kenneth et al, 2016;Mensah et al, 2013;Nyarko et al, 2011;Salifu et al, 2007;Bhattarai & Armah, 2005;Opoku-Afari et al, 2004;Gyimah-Brempon & Gyapong, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretically, inflation is expected to have a positive sign and hence an appreciating effect on the real exchange rate. Thus, an increase in prices may come as result of a rise in demand in both the tradable and non-tradable sectors which can cause the real exchange rate to appreciate [15].…”
Section: Inflationmentioning
confidence: 99%